Effect of K Substitutions on Structural and Superconducting Properties in Bi1.6Pb0.4Sr2-xKxCa2Cu3O10+ Compounds - Hai Duc, Tran; The An, Pham; Thi Kim Anh, Do; Hoang Linh, Vu; Hoang Ha, Pham; Khac Man, Nguyen (VNU Journal of Science: Mathematics - Physics, 2019)
Abstract: Effect of K substitutions on structural and superconducting properties in Bi-Pb-Sr-Ca-Cu-O (BPSCCO) system has been investigated. Bulk Bi 1.6 Pb 0.4 Sr 2-x K x Ca 2 Cu 3 O 10+ d (where x = 0.00; 0.04; 0.08 and 0.1) samples were fabricated by using the solid-state reaction method. Structural properties of the samples were examined by X-ray diffraction (XRD), scanning electron microscopy (SEM) and energy dispersive spectroscopy (EDS) measurement. All samples showed co-existence of  Bi-2223 and Bi-2212 superconducting phases. Interestingly, a formation of the Bi-2223 was decelerated and that of the Bi-2212 was accelerated with increasing K content (x). Superconducting properties of the samples were characterized by using temperature dependences of resistance and field dependences of magnetization data. Both onset and offset transition temperatures were found to decrease, those were correlated to the decreases in residual resistance ratio (RRR). The 65 K magnetization curves of K- substituted samples were enlarged in comparison with that of the pure one. Enlargements of the magnetization curves were possibly attributed to the appearance of additional point-like defects generated by substitutions of K into Sr site. Keywords: BPSCCO, substitutions, flux pinning, defects. References [1] H. Maeda, Y. Tanaka, M. Fukutomi, T. Asano, Jpn. J. Appl. Phys. 27 (1988) L209 – L210. [2] M.H. Mohammed, R. Awad, A.I. Abou - Aly, I.H. Ibrahim, M.S. Hassan, Materials Sciences and Applications 3 (2012) 224 – 233. [3] S.E. M. Ghahfarokhi, M. Z. Shoushtari, Physica B. 405 (22) (2010) 4643 – 4649. [4] C.N.R. Rao, L. Ganapathi, R. Vijayaraghavan, G.R. Rao, K. Murthy, R.A. Mohan Ram, Physica C. 156(5) (1988) 827 – 833. [5] S.A. Sunshine, T. Siegrist, L.F. Schneemeyer, D.W. Murphy, R.J. Cava, B. Batlogg, R.B. van Dover, R.M. Fleming, S.H. Glarum, S. Nakahara, R. Farrow, J.J. Krajewski, S.M. Zahurak, J.V. Waszczak, J.H. Marshall, P. Marsh, L.W. Rupp, Jr., W.F. Peck, Structure and physical properties of single crystals of the 84-K superconductor Bi2.2Sr2Ca0.8Cu2O8+δ , Phys. Rev. B. 38 (1988) 893 – 896. [6] M. Takano, J. Takada, K. Oda, H. Kitaguchi, Y. Miura, Y. Ikeda, Y. Tomii, H. Mazaki, High-Tc Phase Promoted and Stabilized in the Bi, Pb-Sr-Ca-Cu-O System, Jpn. J. Appl. Phys. 27 (1988) L1041 – L1043. [7] C. Michel, M. Hervieu, M. M. Borel, A. Grandin, F. Deslandes, J. Provost, B. Raveau, Superconductivity in the Bi - Sr - Cu - O system, Zeitschrift für Physik B Condensed Matter 68 (4) (1987) 421 – 423. [8] J. Akimitsu, A. Yamazaki, H. Sawa, H. Fujiki, Superconductivity in the Bi - Sr - Cu - O system, Jpn. J. Appl. Phys. 26 (12) (1987) L2080 – L2008. [9] B. Ozkurt, Improvement of the critical current density in Bi-2223 ceramics by sodium–silver co-doping, J. Mater. Sci.: Mater. Electron. 25 (2014) 3295 – 3300. [10] O. Bilgili, Y. Selamet, K. Kocabas, Effects of Li Substitution in Bi-2223 Superconductors, J. Supercond. Nov. Magn. 21 (2008) 439 – 449. [11] M. Ebru Kır, B. Özkurt and M. Ersin Aytekin, The effect of K-na co-doping on the formation and particle size of Bi-2212 phase, Physica B 490 (2016) 79 – 85. [12] H.Y. Wu, K.Q. Ruan, J. Yin, S.L. Huang, Z.M. Lv, M. Li, L.Z. Cao, Effect of K and Nd substitutions on superconductivity of Bi2223 superconductors, Supercond. Sci. Technol. 20 (2007) 1189 – 1192. [13] A.K. Pradhan, S.B. Roy, P. Chaddah, C. Chen, B.M. Wanklyn, Magnetic properties of single-crystal Bi2Sr2CaCu2O8+y: Experimental evidence for a dimensional crossover, Phys. Rev. B 49 (1994) 12984 – 12989. [14] A. Biju, K. Vinod, P.M. Sarun, U. Syamaprasad, Highly enhanced flux pinning in Pb and rare earth codoped Bi-2212, Appl. Phys. Lett. 90 (2007) 072505. [15] S. Vinu, P.M. Sarun, R. Shabna, A. Biju, U. Syamaprasad, Enhancement of critical current density and flux pinning properties of Gd-doped (Bi,Pb)-2212 superconductor, J. Appl. Phys. 104 (2008) 043905. [16] Y.L. Chen, R. Stevens, 2223 Phase Formation in Bi(Pb)─Sr─C─a─Cu─O: II, The Role of Temperature—Reaction Mechanism, J. Am. Ceram. Soc. 75(5) (1992) 1150 - 1159. [17] H. Sozeri, N. Ghazanfari, H. Ozkan, A. Kilic, Enhancement in the high-Tc phase of BSCCO superconductors by Nb addition, Supercond. Sci. Technol. 20 (2007) 522 – 528. [18] S. Hirano, Y. Wakasa, A. Saka, S. Yoshizawa, Y. Oya-Seimiya, Y. Hishinuma, A. Nishimura, A. Matsumoto, H. Kumakura, Preparation of Bi-2223 bulk composed with silver-alloy wire, Physica C 458 (2003) 392 – 396. [19] G. Yildirim, Determination of optimum diffusion annealing temperature for Au surface-layered Bi-2212 ceramics and dependence of transition temperatures on disorders, J. Alloy. Compd. 699 (2017) 247 – 255. [20] B. Ozkurt, Structural and magnetic properties of Li and Na added Bi1.8Sr2.1(Li,Na)xCa1.1Cu2.2Oy (Bi-2212) ceramics (x = 0, 0.05, 0.1 and 0.2), J. Mater Sci, Mater Electron 28 (2017) 8857 - 8863.